Effects of mix vegetation and root shear strength grown on carbonaceous shale - Md Isa, Isharudin; Shamshuddin, Jusop; Khairuddin, Mohd Nizar (Science Alert, 2017)
Background: Carbonaceous shale is one of the common rock types in Malaysia. The most common types of landslides in Malaysia were happened on the cut slope before the construction of highway. Brachiaria ruziziensis and Colopogonium mucunoides were used as the mix vegetation to investigate the effect of chemical amendments on plant growth and root shear strength relationship. Objective: The objective of this study: (1) To investigate the effect of compound fertilizer nitrogen, phosphorus, potassium (NPK), NPK+Ground Magnesium Limestone (GML) (NGL), NPK+GML+foliar fertilizer (Vita-Grow™) (NGF) and control (Ctrl) and (2) To determine the soil shear strength, biomass and root growth. Materials and Methods: The soil samples were analyzed for pH, Total Nitrogen (TN), Soil Organic Carbon (SOC), available phosphorus, exchangeable Al, Ca, Mg and K and trace nutrients (Fe, Mn, Cu and Zn). Results: The carbonaceous shale was low in pH, total N, soil organic carbon, extractable P, basic cations (Ca, Mg and K) and micronutrients (Fe, Cu and Zn). Both P and Ca/Mg were low indicating inherent infertility and chemical constraints for root developments. The dry matter yield, root length and root weight of Brachiaria ruziziensis and Colopogonium mucunoides were increased significantly against NGF treatment. The increased of plant top and root dry weight treated with NGF were 26 and 38%, respectively, compared to the other treatments. The significant root shear strength relationship indicates that root enhanced shear strength by reducing the cohesion and increased the angle of internal friction component. The shear strength analysis from the direct shear test method is to determine the shear strength from the plotted graph. The shear strength analysis showed that NGF treatment was having high shear strength in 5.4, 10.9 and 16.3 and normal stress in 54, 109 and 163 kN m–2. Rapid vegetation growth observed within a 5 months period demonstrated that nutrient and lime application effectively ameliorated chemical constraints to plant growth. Conclusion: The plant mix species treated with NPK+GML+foliar fertilizer (NGF) indicated higher shear strength, dry matter yield and root densities in all layers.